Study protocol: the Fueling Learning through Exercise (FLEX) study – a randomized controlled trial of the impact of school-based physical activity programs on children's physical activity, cognitive function, and academic achievement. (December 2016) - Wright, Catherine; Duquesnay, Paula; Anzman-Frasca, Stephanie; Chomitz, Virginia; Chui, Kenneth; Economos, Christina; Langevin, Elizabeth; Nelson, Miriam; Sacheck, Jennifer
Abstract Background Physical activity (PA) is critical to preventing childhood obesity and contributes to children's overall physical and cognitive health, yet fewer than half of all children achieve the recommended 60 min per day of moderate-to-vigorous physical activity (MVPA). Schools are an ideal setting to meeting PA guidelines, but competing demands and limited resources have impacted PA opportunities. The Fueling Learning through Exercise (FLEX) Study is a randomized controlled trial that will evaluate the impact of two innovative school-based PA programs on children's MVPA, cognitive function, and academic outcomes. Methods Twenty-four public elementary schools from low-income, ethnically diverse communities around Massachusetts were recruited and randomized to receive either100 Mile Club® (walking/running program) orJust Move™ (classroom-based PA program) intervention, or control. Schoolchildren (grades 3–4, approximately 50 per school) were recruited to participate in evaluation. Primary outcome measures include PA via 7-day accelerometry (Actigraph GT3X+ and wGT3X-BT), cognitive assessments, and academic achievement via state standardized test scores. Additional measures include height and weight, surveys assessing psycho-social factors related to PA, and dietary intake. School-level surveys assess PA infrastructure and resources and intervention implementation. Data are collected at baseline, mid-point (5–6 months post-baseline), and post-intervention (approximately 1.5 years post-baseline). Demographic data were collected by parents/caregivers at baseline. Mixed-effect models will test the short- and long-term effects of both programs on minutes spent in MVPA, as well as secondary outcomes including cognitive and academic outcomes. Discussion The FLEX study will evaluate strategies for increasing children's MVPA through two innovative, low-cost, school-based PA programs as well as their impact on children's cognitive functioning and academic success. Demonstration of a relationship between school-based MVPA with neutral or improved, rather than diminished, academic outcomes in a naturalistic environment has the potential to positively influence investment in school PA programs and initiatives. Trial registration ClinicalTrials.gov Identifier:NCT02810834 . Registered May 11, 2015. (Retrospectively registered)